Crisis? Which Crisis? The state of education in Western Australia - Millett, Stephan; Tapper, Alan (John Curtin Institute of Public Policy, Curtin University of Technology, 2009)
In recent years Western Australia has experienced fierce controversy over education, focused almost entirely on the introduction of an 'outcomes-based' approach to curriculum and teaching in upper secondary schools. It was a controversy that generated far more heat than light, with very little in the way of evidence being presented. Good evidence exists on the academic performance of Western Australian students. We summarise this evidence, and argue that it gives no indication that outcomes-based education is either detrimental or beneficial to student performance. In general, WA students perform well in three kinds of internationally benchmarked testing. The 'educational crisis' fever that was created by the news media and some commentators has no justification. If there is serious cause for concern, it is about falling entry standards amongst recruits to the teaching profession. We present the evidence for this fall and argue that, since good teaching is the best guarantee of continuing current academic standards, there is a need to raise the standard of teaching recruitment. This is especially so for the lowest-performing schools, where the best teachers are most needed.